A study on mataphorical expressions in English advertising slogans from the semantic approach = Nghiên cứu các biểu thức ẩn dụ sử dụng trong các khẩu hiệu quảng cáo bằng tiếng Anh từ phương diện ngữ dụng học. M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Chi Mai (University of Languages and International Studies, 2017)
Chapter I: Theoretical background: metaphors and the use of metaphors in advertising. Chapter II: An analysis on metaphor exploitation in advertising slogans. Chapter III: Results and findings. Chapter IV: Summary and conclusion.